Surgical Reconstruction of Lower Face Degloving - Pinto Faria, Paulo Esteves; Gomes de Souza Carvalho, Abrahao Cavalcante; Masalskas, Barbara; Chihara, Leticia; Sant'Ana, Eduardo; Magro Filho, Osvaldo [UNESP] (Lippincott Williams & Wilkins, 2016)
One of the most impressive soft tissue injuries is the facial degloving, normally associated with industrial machines and traffic accidents. This injury is characterized by the separation of the skin and cartilage from the bones, compromising the soft tissues correlated in the trauma area, nerves, and blood vessels. A 28-year-old patient, male, was referred to Aracatuba's Santa Casa Hospital, after a motorcycle accident, hitting his face on the sidewalk. The patient was conscious, oriented, denying fainting and unconsciousness during the accident, and complaining of pain in the nasal region of the face. The suture of wounds was performed using 5-0 absorbable sutures for muscle planes, and reconstruction of the septum and nasal cartilages. The skin was sutured with interrupted stitches using 6-0 nylon. After reducing the edema, a slight increase in alar base was observed. Subsequently, the alar base cinch suture was performed aiming to bring the alar bases to a measure of 34.0mm in diameter. As a conclusion, the knowledge of the anatomy of the region involved, the healing of tissues, and suture techniques for the facial region process were critical to the successful treatment. The evaluation of the alar base in degloving cases can involve aesthetic features.
Keywords: Alar base cinch suture; facial degloving; facial trauma